A Focus on Fire Fundamentals Including Emergency Response Training at the National Fire Agency in Taiwan. Issue 1 (8th February 2013) - Willey, Ronald J.; Hsiao, Jack Huan‐Chang; Sanders, Roy E.; Kossoy, Arcady; Shu, Chi‐Min
<x xml:space="preserve">Abstract</x> This article reflects on process safety fundamentals of fires and explosions for the benefit of new professionals entering the field. It provides a brief review of fire fundamentals such as the fire triangle and the respect that must be paid to the unknown ignition source. Various control methods are reviewed at the elementary level, including the reminder that the ignition source is always free. After a review of fire fundamentals, an emergency response training exercise is presented for a burning propane fire witnessed at a training facility in Taiwan. The National Fire Agency of Taiwan has built the third largest emergency response‐training center in the world. The 270 acres facility is located in central Taiwan near Taichung, Taiwan. The site has 49 separate emergency response training scenarios. Scenario pads include training for fire attack on mock‐ups of chemical storage facilities, tanker trucks, power transformers, passenger airliners, and shipping vessels. Overall, this article serves as a reminder of the safe guards used in fire safety and the importance of training beforehand in the event of an emergency. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 2–7, 2013